Bond-slip behavior of steel reinforced UHPC under flexure: Experiment and prediction. (October 2022) - Shao, Yi; Ostertag, Claudia P.
Abstract: Ultra-high performance concrete (UHPC) is an advanced class of concrete materials that show superior mechanical and durability performance. While several studies have investigated the bond-slip behavior of steel reinforced UHPC using pullout tests, very limited information is available on the bond-slip behavior of reinforced UHPC from beam-type tests, which produce flexural stress states commonly seen in structural members. This study experimentally examines the local bond-slip behavior of reinforced UHPC using beam-end tests. The test variables include UHPC material designs (one low-cement, green UHPC mix and one typical UHPC mix), fiber volumes (0%, 0.5%, and 1.0%), cover thickness (16 mm–51 mm), steel bar sizes (16 mm–32 mm), and test ages (3 days and 50 days). A total of thirty-two tests are conducted. While the non-fiber UHPC specimens fail in a brittle manner due to splitting failure, all fiber-reinforced UHPC specimens exhibit confined splitting failure and ductile bond-slip responses. The peak bond strength is found to exhibit a linear relationship with the cover-thickness-to-bar-diameter ratio and the square root of UHPC compressive strength. Furthermore, a local bond-slip model is developed, which includes a new bond-strength prediction method that predicts the experimental results with a mean absolute error of 7.6%. Finally, this local bond-slip model is combined with a partial interaction model to explore the global bond stress variations under different embedment lengths and flexural states. Equations are proposed to predict the development length that can lead to reinforcement yielding with minimized bonded length or minimized global slip.